A palaeohydrological record of a complete Eemian series from Żabieniec Ża-19 (Garwolin Plain, Central Poland) with reference to palaeoclimate data - Żarski, Marcin; Kultys, Kamil; Mirosław-Grabowska, Joanna; Zalat, Abdelfattah; Hrynowiecka, Anna; Łabęcka, Karolina; Terpiłowski, Sławomir; Pidek, Irena Agnieszka (Acta Geologica Polonica, 2023)
The aim of this study was to reconstruct the evolution of the Eemian palaeolake in the Żabieniec site (Garwolin Plain, Central Poland); it identifies changes in the water level and the trophic status of the lake resulting from panregional factors, including climate changes occurring during individual phases of the last interglacial, and local geologic-geomorphological factors shaping the palaeoenvironment using multi-proxy methods (palaeobotanical analyses, subfossil Cladocera and diatoms analyses as well as determinations of the stable isotopes). A record was obtained of all seven Regional Pollen Assemblage Zones (RPAZs) according to Mamakowa’s description of the Eemian pollen succession (1989), and of the changes in microfossil assemblages and isotopes in palaeolake sediments associated with lake evolution. Special attention was paid to the Middle Eemian RPAZ 4 (i.e. hazel phase) of the climatic optimum; all proxies associate this with the highest water level and a warm humid climate. During the E5/E6 RPAZs, the eutrophic lake transformed very quickly, and a transitional peatbog was formed. The higher humidity of the late Eemian resulted in another increase in water level. The multi-proxy record of the Żabieniec palaeolake which we obtained was compared to those of other Eemian water bodies in the Garwolin Plain and in Central Poland that exhibit sedimentation gaps especially during the younger part of the E5 RPAZ.
Keywords: Eemian Interglacial; fossil lakes; Multi-proxy analyses; climate changes; central Poland